Tribological Evaluation of Biomimetic Shark Skin with Poly-DL-Lactic Acid (PDLLA) Nanosheets with Human Fingerprint Sliding Behavior - Shunsuke, Nakano; Mohd Danial, Ibrahim; Dayang Salyani, Abang Mahmod; Masayuki, Ochiai; Satoru, Iwamori (MDPI, 2025)
This study evaluates the tribological properties of poly-DL-lactic acid (PDLLA) nanosheets attached to shark-skin surfaces with varying textures. The main goal was to assess friction reduction in samples with different surface textures and investigate the inﬂuence of PDLLA nanosheets on tribological behaviors. Biomimetic shark skin was created using a polydimethylsiloxane (PDMS)-embedded stamping method (PEES) that replicates shark skin’s unique texture, which reduces friction and drag in aquatic environments. PDLLA nanosheets, with a controlled thickness of several tens of nanometers, were fabricated and attached to the PDMS surfaces. The morphological characteristics of the materials were analyzed before and after attaching the PDLLA nanosheets using scanning electron microscopy (SEM), revealing the uniformity and adherence of the nanosheets to the PDMS surfaces. Friction tests were conducted using force transducers to measure the friction coefﬁcients of biomimetic shark skin, biological models, and ﬂat PDMS and silicon substrates, allowing a comprehensive comparison of frictional properties. Additionally, sliding tests with human ﬁngers were performed to assess friction coefﬁcients between various ﬁngerprint shapes and sample surfaces. This aspect of the study is critical for understanding how human skin interacts with biomimetic materials in real-world applications, such as wearable de-vices. These ﬁndings clarify the relationship between surface texture, nanosheets, and their tribological performance against human skin, thereby contributing to the development of materials with enhanced friction-reducing properties for applications such as surface coatings, substrates for wearable devices, and wound dressings.